IMPLEMENTASI SISTEM PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI KOTA SAMARINDA - M . Makhradi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
Abstract              This study aims to describe the implementation of the system of land and building tax collection is done at the Regional Revenue Office Samarinda and how efforts to prevent leakage of land and building tax results in Samarinda.              Writing this law included in the writing of an empiricial law that is descriptive. The research location in the Regional Revenue Office Samarinda, East Kalimantan. The data used are primary data and secondary data. Sources of primary data in the form of interviews with the staff of the office of the Regional Revenue Office Samarinda, and secondary data sources in the form of legislation relating to the problems to be studied and discussed.              Based on the research results obtained that the implementation of land and building tax collection carried out by the Regional Revenue Office Samarinda already of good administration and in accordance with the rules of law No. 28 Year 2009 on Regional Taxes and Levies.              Factors that may hinder the succesful implementation of the collection of land and building tax among others, lack of awareness and understanding of the taxpayer in the register, calculate and report the object yourself tax-controlled, owned and exploited then domicile taxpayers are planted in taxable income, as well as the lack of supervision against officers collector. The steps undertaken to overcome these obstacles is to do counseling, workshops, seminars concerning taxes; reducing payments or tax calculations with the procedures in force; intensify counseling to the people directly, through the mass media inform SPPT when shots can be started and payment limits; by giving a Warning Letter to the taxpayer. Keywords : Implementation of collection System and Building Tax